Estudo de atividades biológicas de óleos essenciais e extratos de espécies do gênero Aniba de interesse cosmético - Nogueira, Jéssica Rodrigues (2015)
The skin is a lining epithelium divided into epidermis, dermis and subcutaneous tissue, whose main functions are the protection and thermal control. In the epidermis the main cell type is the keratinocyte. Another cell type found is the melanocyte, responsible for pigmentation. Continuous sun exposure causes production of reactive oxygen species (ROS) and stimulates the melanocytes to produce more pigment. As a result, it may cause stains on the skin and photoaging. Therefore, there is a need for searching compounds that can combat skin aging, particularly from natural substances. Among the many species from the Amazonian flora, Lauraceae family has stood out for having aromatic species, especially those of the genus Aniba. The Aniba rosaeodora, rosewood, is the best known species of the genus due to the production of an essential oil widely used in the perfume industry, but other species of the same genus are little known, like Aniba parviflora (macacaporanga) and Aniba canelilla (preciosa), and consequently, little is known about the biological activity and the potential of these species for the cosmetic industry. In this study the inhibiting melanogenesis activity of essential oils from A. rosaeodora, A. canelilla and A. parviflora was assessed, as well as the antioxidant activity of A. parviflora extracts and its partitions. The essential oils of leaves and stems were obtained by hydrodistillation. The extracts were macerated in ethanol and fractionated with different solvents (hexane, dichloromethane, ethyl acetate and hydroalcoholic). To evaluate the inhibition of melanogenesis in vitro, tyrosinase inhibition tests using cells and murine melanoma, and dosage of melanin was performed. Cytotoxicity was also evaluated, as well as chemical identification, by gas chromatography coupled with mass spectrometry (GC-MS). To evaluate the antioxidant activity, the radical capture tests with DPPH and ABTS, along with phenols and flavonoids quantification were performed as screening tests for evaluating the production of reactive oxygen species in macrophages, by the method of dichlorofluorescein. The oil from leaves of A. canelilla demonstrated reduction of melanin content in comparison to the control with stimulation of melanogenesis. This oil also presented inhibition of tyrosinase on murine melanoma tests, and showed no cytotoxicity at the higher concentration studied (100 g/mL). The analysis by GC-MS enabled the identification of twenty two essential oil constituents, and 1-nitro-2-phenylethane was the major compound, constituting 87% of the oil. The hydroethanolic and ethyl acetate partitiond obtained from leaves and stems of A. parviflora showed intense antioxidant activity by inhibiting the oxidation of DPPH and ABTS at low concentrations, presenting significant amount of phenols and flavonoids. The method of dichlorofluorocein confirmed the antioxidant activity by the reduction of ROS even at the lowest study concentration of 6.25 g/mL in keratinocytes, without presenting cytotoxicity at the same concentration. Based on these results, this study proves that these Amazonian species have the potential to be explored by the cosmeceutical industry, thus adding value to Amazon products for research, development and innovation. Keywords: photo-aging, antioxidant, phyto-cosmetic, Lauraceae.